PELATIHAN PERENCANAAN KEUANGAN KELUARGA PASCA ERA KRISIS KESEHATAN - Natalia, Irene (Bajang Institute, 2024)
This community service activity aims to help reorganize finances after the health crisis era (post-COVID-19 pandemic). Financial planning needs to be carried out by all community, including families affected by the COVID-19 pandemic. This training activity is carried out by providing conceptual knowledge and skills in financial planning so that participants can recover and improve individual and family financial goals. The partners who assisted in this activity were mindfulness meditation practitioner groups. The main target is to provide an understanding of family financial planning. This training activity provides material and discussions about the family life cycle, measures of healthy household financial conditions, better family financial planning and management, solutions for unhealthy financial health examination results, and family budget planning and preparation. The activity’s results can benefit partners because the concept and skills of financial planning provide improvements and enhancements to the quality of family financial plans among COVID-19 survivors.